THE EFFECT OF ETHICAL ORIENTATION AND ETHICAL EDUCATION ON THE PERCEPTION OF UNETHICAL BEHAVIOR OF ACCOUNTING STUDENTS - Aryani Intan Endah Rahmawati (Jurnal Akuntansi dan Pajak, 2022)
Many cases of accounting fraud in Indonesia occur in public, private companies, and even accounting firms. These cases have eroded public confidence in the accounting profession. Lack of implementation of professional ethics has been studied extensively as the cause of these frauds. This requires the cultivation of ethics since they were in college. This requires the cultivation of ethics while accounting students are still studying in university. The perception of students as future leaders can provide employers with information on how they will make ethical decisions when faced with similar situations in the business world. Ethical orientation and ethical education were investigated as factors influencing the ethical perception of accounting students using a survey method. The interaction of the two was also investigated and resulted in the finding that students who were idealistic and received ethics education had lower perceptions of unethical behavior than students who were relativist and did not receive ethics education. Additional analysis showed that gender had no effect on students' ethical perceptions.